Derecho y política agrarios y agroalimentarios - Pastorino, Leonardo Fabio (Wydawnictwo Naukowe UAM, 2017)
The specifics of agricultural activity entails a necessity to adopt for it a special regulation in the form of agricultural law. The performance of agricultural activity is a contributory factor to co-occurrence of a number of relationships shaping the contemporary agricultural structure which in the event of incompliance with the economic, social or environmental goals leads to a situation which Antonio Vivanco termed ‘structural deficiencies’. Their appearance sometimes enforces State intervention which then frequently means adoption of new legal instruments in the sphere of agricultural law. A look at this phenomenon globally from the perspective of the production chain leads to a conclusion that it refers to the agro-industrial and agro-food sectors, which means that a focus is put on the inter-relations in the production chain and especially on the relationships between agricultural produce markets and agricultural producers. The aim of this paper is to describe these issues on the example of Argentina. An analysis is also made on the usually disadvantageous situation of the primary producers in comparison with the other participants of the production chain. The need for a thought on the possibility of classifying agricultural production as one of the elements safeguarding public order has been emphasised.

La specificità delle attività agricole porta alla necessità di dedicargli una regolazione speciale sotto forma di diritto agrario. L’esercizio dell’attività agricola contribuisce infatti alla coesistenza di rapporti materiali e formali, che influenzano la struttura agricola contemporanea, la quale, in caso di incompatibilità con gli obiettivi economici, sociali, ambientali, crea una situazione, chiamata da Antonio Vivanco, „difetti/carenze strutturali”. L’emergere di questo fenomeno in qualche modo impone allo Stato di intervenire, il che spesso si manifesta con l’adozione di nuovi strumenti giuridici in materia agricola. La valutazione di questo fenomeno su scala mondiale dal punto di vista della filiera di produzione porta a concludere che esso si riferisce al settore agroindustriale e agroalimentare, il che porta l’attenzione su interconnessioni presenti nella filiera di produzione, e in particolare ad occuparsi dei rapporti che intercorrono tra i mercati dei prodotti agricoli e i produttori agricoli. L’articolo si propone di mostrare le problematiche sopra indicate sull’esempio dell’Argentina. Nello studio all’analisi è stata sottoposta una situazione svantaggiata in cui si trovano i produttori primari rispetto ad altri attori della filiera produttiva. L’autore ha cercato inoltre di sottolineare l’importanza di prendere in considerazione la necessità di qualificare la produzione agricola come uno degli elementi chiave per garantire l’ordine pubblico.
Agricultural law and agro-food policies
Il diritto agrario e le politiche agricole alimentari